Тепловые методы восстановления сыпучести смерзшихся грузов - Виноградова, Т.В.; Троценко, Л.Н.; Пикашов, В.С. (Энерготехнологии и ресурсосбережение, 2014)
Представлен анализ существующих методов восстановления сыпучести смерзшихся транспортируемых дисперсных материалов. Профилактические методы осуществляются в местах погрузки насыпных материалов. К восстанавливающим сыпучесть относятся механические и тепловые методы. Механическое рыхление осуществляется при помощи различных рабочих органов: клиньев, рыхлящих приспособлений, скребков, буров, фрез и др. Тепловой разогрев осуществляют в специальных гаражах при помощи электрических и радиационных нагревателей, а также потоком теплоносителя. Показано, что тепловой разогрев материалов целесообразен при наличии в пунктах приема вагоноопрокидователей и определенных источников тепла (природный, доменный газ, пар и др.) для быстрой разгрузки большого количества вагонов. При этом допускается частичное восстановление сыпучести груза, так как для этого достаточно оттаивания тонкого слоя материала, примерзшего к внутренним стенкам и днищу вагона. Приведены классификация существующих методов, выводы по каждому из представленных методов, а также некоторые их сравнительные характеристики. Представлено аналіз існуючих методів відновлення сипучості змерзлих дисперсних матеріалів, що транспортуються. Профілактичні методи здійснюються у місцях завантаження насипних матеріалів. До відновлюючих сипучість відносяться механічні та теплові методи. Механічне рихлення здійснюється за допомогою різних робочих органів: клинів, пристосувань для рихлення, скребків, бурів, фрез та ін. Тепловий розігрів здійснюють у спеціальних гаражах за допомогою електричних та радіаційних нагрівачів, а також потоком теплоносія. Показано, що тепловий розігрів доцільний при наявності у пунктах прийому вагоноперекидачів та певних джерел тепла (природний, доменний газ, пара та ін.) для швидкого розвантаження великої кількості вагонів. При цьому допускається часткове відновлення сипучості вантажу, оскільки для цього достатньо відтаювання тонкого шару матеріалу, примерзлого до внутрішніх стінок та днища вагону. Наведено класифікацію існуючих методів, висновки щодо кожного з представлених методів, а також деякі їх порівняльні характеристики. The article presents an analysis of existing recovery methods and techniques of frozen transported bulk materials flowability. They are divided into two main groups: preventive and reducing flowability. Preventive methods are used at the loading place of the transported bulk material. Such methods include pre-drying, freezing, spraying of oils and prevention liquids, filling by limestone and sawdust, equipping railway cars by heaters and others. The methods of flowability recovery include mechanical and thermal methods. Mechanical opening is carried out with the help of various operative parts such as wedges, ripper devices, scrapers, drill, milling cutters and others. Thermal heating is carried out in special garages by means of electric and radiation heaters, as well as heat carrier flow. Based on the analysis of long-term experience in the application of various recovery methods of frozen transported bulk materials flowability it may be concluded the following. Mechanical rippers are used for weakly frozen nonplastic loads, when its heterogeneity is acceptable by fraction after treatment. Thermal heating is reasonable when car dumper and specific sources of heat (natural gas, blast furnace gas, steam, et al.) are available in collection points, when it necessary to unload quickly a large number of rail cars. At that a partial recovery flowability is accepted because it is enough to thaw a thin layer of material, frozen to the inner walls and the bottom of the rail car. As a result of this analysis, the article presents a classification of existing methods, the conclusions for each of he presented methods, as well as some of their comparative characteristics.